Pendidikan Anti Korupsi melalui Hidden Curriculum dan Pendidikan Moral - Salistina, Dewi (Taallum: Jurnal Pendidikan Islam, 2015)
This article is intended to elaborate strategies in incorporating anti corruption awareness through hidden curriculum and morality education. It is of necessity to increase such kind of awareness among students so that they can avoid any action related to corruption. In this case, some practices such as good behavior, discipline, and good relationship among students-teachers are fostered in the daily activities at school. The effect is the increase of studentsâ honesty, responsibility, and solidarity across level of education.